Lipids [ nutrition and health - Leray, Claude (CRC Press, 2015)
Lipids (fats and oils) are essential cellular components in animals, plants, and bacteria, and they play an important role in human nutrition. This book presents a detailed account of the nutritional aspects of all types of lipid-fatty acids, triacylglycerols, phospholipids, sphingolipids, sterols, and fat-soluble vitamins (A, D, E, K). The importance of the omega-3/omega-6 fatty acid ratio in cardiovascular health is well known, but the nutritional balance of lipids also impacts the immune system, the central nervous system, and cancer processes